Apportionment of damages for contributory negligence: a fixed or discretionary approach?. (14th April 2015) - Goudkamp, James
Abstract : In most of the common‐law world, legislation provides for damages to be apportioned where the claimant is guilty of contributory negligence. This legislation gives judges considerable latitude to determine the extent to which damages should be diminished for contributory negligence. It imposes what will be called a system of 'discretionary apportionment'. This paper draws attention to the fact that, although most common‐law jurisdictions are, by virtue of their apportionment legislation, in the thrall of the paradigm of discretionary apportionment, there are many, varied departures from this paradigm. This paper classifies these departures (which will be called 'fixed apportionment rules'), emphasises that they conflict with the apportionment legislation and considers how the conflicts ought to be resolved. An important conclusion reached is that it can plausibly be argued that the landmark decision in Froom v Butcher, at least as it has been understood in subsequent cases, was decided per incuriam . Froom sits uncomfortably with the apportionment legislation. Attention is then turned to the arguments for and against a discretionary system of apportionment as opposed to a system that incorporates more fixed apportionment rules. It is contended that much stands to be gained from introducing more fixed apportionment rules.